What are the perceptions and experiences of adults using mobile applications for self-management in diabetes? A systematic review - Benedict Hayhoe; Azeem Majeed; Geva Greenfield; Ana Luísa Neves; Henock B Taddese; Kalthum Patail; Hui Hsuan Pai (BMJ Open)
Objectives Diabetes mellitus is a chronic disease that entails significant burdens to patients, caregivers and society at large. While self-management behaviours like healthy eating and monitoring of blood glucose help to reduce the care burden, they are still perceived to be burdensome. Mobile applications have emerged as promising digital tools in helping patients to self-manage their conditions. We conducted systematic review to explore the perceptions and experiences of adults with types 1, 2 and gestational diabetes using mobile applications for self-management in diabetes.Design A systematic review of published primary studies exploring perceptions and experiences of adults living with types 1, 2 and gestational diabetes who used/have used mobile applications for self-management. The study was reported following the best practice guidelines defined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Data sources We searched for articles published from January 2007 to December 2023 via MEDLINE (Ovid), Embase (Elsevier), CINAHL (Ovid) and Scopus (Elsevier).Eligibility criteria Primary qualitative studies that describe the perceptions and experiences of adults in using mobile applications in self-management of types 1, 2 and gestational diabetes published between January 2007 and December 2023.Data extraction and synthesis Two independent reviewers screened identified papers for eligibility, extracted data using a pre-defined data extraction form and applied the Critical Appraisal Skills Program tool to appraise the quality of the included studies. Data were narratively synthesised, guided by the ‘unified theory of acceptance and use of technology (UTAUT)’ framework.Results A total of 24 qualitative studies deploying interviews and surveys with open-ended questions were included in the review. We identified four major themes, which were mapped against the constructs of the ‘UTAUT’ framework: ‘performance expectancy’, ‘effort expectancy’, ‘social influence’ and ‘facilitating conditions’.More than 50% of the studies described favourable app features relating to monitoring blood glucose, diet and exercise while also emphasising the importance of customising these to patient needs. About 40% of the studies described unfavourable aspects related to uploading of excessive information, monitoring device incompatibility, episodic app crashes and telephone handling issues.Conclusion The review supports the favourable view of mobile applications as promising tools in helping patients with diabetes to self-manage. However, the challenges on the ease of use and non-customised features of the apps potentially hinder patients’ long-term engagement.